Impact of Puzzle Playing Therapy on Anxiety Levels Among Patients in the St. Theresia Room at St. Elisabeth Hospital in Medan - Mestiana Br. Karo; Elyakim Pasti Selamat Zega (International Journal Of Health Science, 2024)
Introduction: Anxiety is the most frequently observed response in children during their hospitalization. Puzzle play therapy refers to a therapeutic activity that involves children engaging in the process of assembling fragmented pieces to construct a complete picture or to finish a given written task. The purpose of this study is to evaluate the impact of puzzle play therapy on the reduction of anxiety levels among children. Method: This study adopted a pre-experimental design, specifically employing a one-group pretest-posttest approach. The population of the study comprised all pediatric patients aged between 3 and 6 years who were admitted to the hospital. Purposive sampling was used to select a total of 32 participants. The data was collected using a questionnaire as the research instrument. Result: The study's findings revealed that the mean pre-test anxiety score was 25.28, with a standard deviation of 7.040. In comparison, the mean post-test anxiety score was 19.19, with a standard deviation of 4.254. The statistical analysis conducted using the Wilcoxon test showed a ρ value of 0.000 (p < 0.05), which indicates a statistically significant reduction in anxiety levels following the intervention of puzzle play therapy.